PERMUKIMAN ABOGE KRACAK : KEARIFAN LOKAL KOMUNITAS ABOGE DI BANYUMAS - WITA WIDYANDINI; YOHANA NURSRUWENING; BASUKI BASUKI (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2015)
ABSTRACTIslamic Aboge’s settlement in Cikakak Village, Wangon, Banyumas is the centerof the Islamic Aboge community in Banyumas Regency, with spreadingsettlements one of them is located in Kracak Village, Ajibarang, Banyumas. Tothat end, researchers intend to conduct research in order to explore and find theimplementation of the basic concepts of Islamic Aboge’s settlements in CikakakVillage as center of the Islamic Aboge community to the spreading settlements inKracak Village, Ajibarang, Banyumas.The method used is qualitative research methods. As for the method of analysisusing descriptive and comparative methods. The result of this research is IslamicAboge’s settlements in Cikakak Village give effect to the Islamic Aboge’sspreading settlement in Kracak Village, Ajibarang, Banyumas. The applicationof basic concepts Aboge’s settlements Cikakak seen in the arrangement ofsettlement’s element spatial and hierarchy of building, and Aboge communitystill apply the concept of local wisdom on their spatial settlement.Keywords: settlement patterns, local wisdom, Islamic Aboge, KracakVillage